Vibration Control of Flexible Mode for a Beam-Type Substrate Transport Robot. (31st July 2013) - Park, Cheol Hoon; Park, Dong Il; Park, Joo Han
Beam-type substrate transport robots are widely used to handle substrates, especially in the solar cell manufacturing process. To reduce the takt time and increase productivity, accurate position control becomes increasingly important as the size of the substrate increases. However, the vibration caused by the flexible forks in beam-type robots interferes with accurate positioning, which results in long takt times in the manufacturing process. To minimize the vibration and transport substrates on the fork as fast as possible, the trajectories should be prevented from exciting the flexible modes of the forks. For this purpose, a fifth-order polynomial trajectory generator and input shaping were incorporated into the controller of the beam-type robot in this study. The flexible modes of the forks were identified by measuring the frequency response function (FRF), and the input shaping was designed so as not to excite the flexible modes. The controller was implemented by using MATLAB/xPC Target. In this paper, the design procedure of input shaping and its effectiveness for vibration attenuation in both "no load" and "load" cases is presented.